The Role of Leadership, Teaching Factory (TEFA) Program, Competence of Creative Products and Entrepreneurship On Entrepreneurial Interest of the Vocational School Students - Purwanto, Agus; Novitasari, Dewiana; Asbari, Masduki (International Journal of Social and Management Studies, 2022)
This study aims to determine the effect of leadership, teaching factory program (TEFA) & the competence of creative products and vocational school entrepreneurship. Respondents in this study were 453 students of the Vocational school program. Data was collected using primary data, namely a questionnaire about the teaching factory program, interest in entrepreneurship which was distributed to respondents online using social media. Data analysis used path analysis with SPSS software data processing tools. The results of the path analysis of the teaching factory program have a direct positive effect on the competence of creative and entrepreneurial products. The teaching factory program has a direct effect on students' interest in entrepreneurship. Creative product competence and entrepreneurship have a direct positive effect on entrepreneurial interest. With this research, schools should further improve the existing teaching factory program so that it can improve student competence and can also increase students' interest in entrepreneurship.